Impact of Socio-Economic Factors on the Crime Situation. Corruption - Gavelis, Vytautas (Ekonomika, 2001)
In the Lithuanian Republic there has been noticed a dramatically rise of criminality. During 1990-1999 the criminality in Lithuania rase in 2,1 times.The research shows the close correlative connection between the criminality and the social and economical factors (see Table 1).While analyzing the impact of the corruption on the criminality, the article also discusses the factors of the corruptive market formation. The benefit principles are applied to model the economical behavior of a corrupted official. The article also studies the factors disguising the responsibility abuse by a corrupted official.